2012
DOI: 10.1080/19361653.2011.649616
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Cyberbullying: A Descriptive Analysis of the Frequency of and Impact on LGBT and Allied Youth

Abstract: Young people continue to endure school-yard bullying and harassment. In our era of advanced information and communication technologies, however, a new variation has emerged: we now live in the age of cyberbullying. The current study explores the frequency of cyberbullying and its impact on the lives of lesbian, gay, bisexual, transgendered (LGBT), and allied youth. Participants in this national study comprised middle school and high school students between the ages of 11 and 18 years old who identified as lesb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…What remains unclear are the consequences of bullying within each group of sexual minorities. Studies hitherto have not investigated potential differences between such groups, but, rather, have considered SMY as a homogeneous group (Cooper and Blumenfeld, 2012;Varjas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…What remains unclear are the consequences of bullying within each group of sexual minorities. Studies hitherto have not investigated potential differences between such groups, but, rather, have considered SMY as a homogeneous group (Cooper and Blumenfeld, 2012;Varjas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Or, la cyberintimidation peut également exercer beaucoup de pression sur les jeunes ciblés, les laissant avec des sentiments de frustration et de tristesse et les rendant vulnérables au stress et à la démotivation scolaire (Li, 2007). Seule une minorité d'entre eux choisirait cependant de modifier leurs habitudes de navigation (Mason, 2008 (Cooper et Blumfeld, 2012). Ainsi, il est tentant de positionner les technologies de la communication comme le grand égalisateur des forces réelles, qui permet aux victimes de répondre coup pour coup aux agresseurs et qui propulse l'engrenage de la violence.…”
Section: Le Cyberagresseur : Un Nouveau Prédateur ?unclassified
“…Three studies (27.3%) did not report participants' age range [38,39,44]. Seven studies included both male and female participants [35,[37][38][39][40][41][42]. In these studies, the percentage of the samples that reported their sex as female ranged from 55 to 78.1%.…”
Section: Study Characteristics and Appropriate Reportingmentioning
confidence: 99%
“…Two studies included a sample of transgender participants with this group comprising 0.9% [40] and 0.8% [42] of the total. Additionally, two studies included a small sample of gender non-conforming participants.…”
Section: Study Characteristics and Appropriate Reportingmentioning
confidence: 99%
See 1 more Smart Citation